A convenient aqueous copper-catalyzed synthesis of quinazolinones. Issue 29 (22nd July 2015) - Xu, Yulong; Xie, Qiong; Li, Wei; Sun, Hongpeng; Wang, Yonghui; Shao, Liming
Abstract: A simple and highly efficient method for the aqueous copper-catalyzed coupling reactions with the aid of a commercially available surfactant (TPGS-750-M) is reported. In an aqueous micellar medium, 2-halobenzoic acids derivatives reacted with amidines and guanidines and generated the corresponding quinazolinone derivatives in good to excellent yields in the range of room temperature to, at most, 50 °C. In addition, the reaction medium can be recycled, and this method led to a significant improvement of the E factors in comparison with the previously reported process. Graphical abstract: